SISO management in comprehensive schemes in the construction sector (Revista de Investigaciones Universidad del Quindío, 2016)
The document refers to the degree SISO management plans by the companies in the construction sector, research that enables you to determine the applicability of the various programs that make up the comprehensive plan. The methodology used as tool software in java that percentage way evaluates the degree of implementation of each of the programs and suggests the remedies in the case. The results obtained determine the current diagnosis of the sector and enable the design of a control guide that contains a series of activities in accordance with the construction process. The conclusions dealt with aspects of importance of work and proposes a series of recommendations to take into account in future projects to avoid situations or events of emergency in the prevention of injuries and accidents at work.
Keywords: Management; comprehensive plan; programs; unsafe conditions; diagnosis; control; injuries; accidents Guide